2013
DOI: 10.1021/nn305901n
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Interaction and Atomic-Scale Wear of Amplitude Modulation Atomic Force Microscopy Probes

Abstract: Wear is one of the main factors that hinders the performance of probes for atomic force microscopy (AFM), including for the widely used amplitude modulation (AM-AFM) mode. Unfortunately, a comprehensive scientific understanding of nanoscale wear is lacking. We have developed a protocol for conducting consistent and quantitative AM-AFM wear experiments. The protocol involves controlling the tip-sample interaction regime during AM-AFM scanning, determining the tip-sample contact geometry, calculating the peak re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…S1. A reported disadvantage of blind tip reconstruction is that typically only a small region of the tip around the apex can be resolved (~10 nm)1011, however by using the high roughness surfaces reported in this study we are able to reconstruct tip shapes up to 100 nm below the apex. Clearly, we can observe an increase in the radius of the tip, before and after wear.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…S1. A reported disadvantage of blind tip reconstruction is that typically only a small region of the tip around the apex can be resolved (~10 nm)1011, however by using the high roughness surfaces reported in this study we are able to reconstruct tip shapes up to 100 nm below the apex. Clearly, we can observe an increase in the radius of the tip, before and after wear.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, AFM tip wear is a process that is currently subject of extensive research, using various tip materials and AFM operating modes67. Tip wear can occur by several mechanisms, such as adhesive wear8, abrasive wear8, fracture910 and plastic deformation11. Recently, it was found that nanoscale wear with low forces can be described accurately based on an atom-by-atom attrition process, which implies a very gradual wear mechanism12131415.…”
mentioning
confidence: 99%
“…[ 17 ] A few scanning tunneling microscopy (STM) observations on spin-state switching phenomena have also been published. [ 28 ] In this study, the authors show that the radius of the silicon tip changes from the fi rst scan, and after nine scans the radius is doubled. Here, we describe a completely different approach, based on the strong electron-lattice coupling in these compounds, wherein we determine the spin-state dependence of the Young's modulus ( E ) and use this property for high-spatial-resolution imaging of the spin transition.…”
mentioning
confidence: 65%
“…[ 28 ] In this study, the authors show that the radius of the silicon tip changes from the fi rst scan, and after nine scans the radius is doubled. For a quantitative study of the mechanical properties during the course of a phase transition (i.e., through a large number of scans) in relatively stiff materials, the wearing of the tip becomes a critical issue.…”
mentioning
confidence: 65%
“…We deduce a rule to image soft materials with a lateral resolution below 3 nm that involves the application of forces in the sub-100 pN regime, the use of cantilevers with force constants below 0.1 N/m, free amplitudes below 2 nm and relative sharp tips ( R t ≤ 5nm). AM-AFM operation at relatively high amplitudes can also lead to tip blunting [3536]. The estimation of the peak force prior to performing the experiment could prevent tip damage.…”
Section: Introductionmentioning
confidence: 99%